1995
DOI: 10.1111/j.1365-246x.1995.tb05729.x
|View full text |Cite
|
Sign up to set email alerts
|

Waveform response to the morphology of 2-D subducted slabs

Abstract: S U M M A R YTo evaluate waveform responses to morphological variations of the subducted lithospheric slab, scalar waveform solutions are computed for 2-D slab models perpendicular to the arc. The dependence of the waveforms on the background 1-D velocity model and on the wavelet frequency is analysed. The waveform variation due to the background velocity model is characterized by gradual changes in amplitude and traveltime over the take-off angle; such variation can be distinguished from the slab-generated wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…It has long been observed that sharp structures have profound effects on waveforms, and that such waveform complexity can be used as an independent constraint on slab structure. There have been a few attempts to use 2‐D and 3‐D forward modeling to investigate the effects of slab geometry and heterogeneity on waveforms [ Zhou and Chen , 1995; Vidale , 1987; Igel et al , 2002]. Some preliminary results based upon broadband sparse data coverage were obtained for slabs in other subduction zones, such as the slabs beneath North America [ Vidale and Garcia‐Gonzalez , 1988] and Kuril‐Kamchatka [ Cormier , 1989].…”
Section: Introductionmentioning
confidence: 99%
“…It has long been observed that sharp structures have profound effects on waveforms, and that such waveform complexity can be used as an independent constraint on slab structure. There have been a few attempts to use 2‐D and 3‐D forward modeling to investigate the effects of slab geometry and heterogeneity on waveforms [ Zhou and Chen , 1995; Vidale , 1987; Igel et al , 2002]. Some preliminary results based upon broadband sparse data coverage were obtained for slabs in other subduction zones, such as the slabs beneath North America [ Vidale and Garcia‐Gonzalez , 1988] and Kuril‐Kamchatka [ Cormier , 1989].…”
Section: Introductionmentioning
confidence: 99%
“…The A-A cross-section shows the S (upper) and ScS (lower) ray paths and depths at which they pierce the other transects (black vertical lines). Zhou & Chen (1995) showed that the waveform effects because of a slab having a 2 per cent increase in V S compared to the surrounding mantle (as is imaged in tomography models) are very difficult to detect compared to a slab with a 10 per cent V S contrast. Cross-sections B-B through E-E show the piercing location of S (cross) and ScS (circle).…”
Section: Discussionmentioning
confidence: 99%
“…However, the strength of velocity heterogeneity in TXBW is probably underestimated because of the smoothing imparted in the inversion process. Zhou & Chen (1995) showed that the waveform effects because of a slab having a 2 per cent increase in V S compared to the surrounding mantle (as is imaged in tomography models) are very difficult to detect compared to a slab with a 10 per cent V S contrast. Future work should consider realistic 3-D subducted slab geometries with stronger velocity contrasts.…”
Section: Discussionmentioning
confidence: 99%
“…As pointed out by Vidale (1987) and Cormier (1989), source-side slab diffraction/multipathing causes waveform distortion recorded teleseismically, such as S and ScS, and also causes focusing and defocusing at teleseismic distances (Vidale 1987;Cormier 1989;Weber 1990;Sekiguchi 1992;Perrot et al 1994;Zhou & Chen 1995). Such waveform effects and amplitude perturbation due to the high-velocity slab have often been used to constrain the geometry and depth of the slab near the source side.…”
Section: F I N I T E D I F F E R E N C E M O D E L L I N Gmentioning
confidence: 99%